1988
DOI: 10.1111/j.1432-1033.1988.tb14200.x
|View full text |Cite
|
Sign up to set email alerts
|

3‐Methyladenine, an inhibitor of autophagy, has multiple effects on metabolism

Abstract: 3-Methyladenine is generally used as an inhibitor of autophagy [P. 0. Seglen & P. B. Gordon (1982) Proc.Natl Acad. Sci. U S A 79, . Using isolated hepatocytes, we observed that 3-methyladenine has other effects as well.1. 3-Methyladenine promoted glycogen breakdown and inhibited flux through phosphofructokinase and pyruvate kinase. These effects proved to be unrelated to inhibition of autophagic proteolysis and were caused by CAMP, which slightly increased in the presence of 3-methyladenine.2. Addition of 3-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 27 publications
3
85
1
Order By: Relevance
“…[174][175][176] Similarly, 3-methyladenine affects multiple facets of cellular metabolism. 177 Thus, while tests with pharmacological inhibitors constitute useful starting points for experimentation, they cannot be employed as surrogates of genetic studies based on gene knockout or RNAi.…”
Section: Notes Of Cautionmentioning
confidence: 99%
“…[174][175][176] Similarly, 3-methyladenine affects multiple facets of cellular metabolism. 177 Thus, while tests with pharmacological inhibitors constitute useful starting points for experimentation, they cannot be employed as surrogates of genetic studies based on gene knockout or RNAi.…”
Section: Notes Of Cautionmentioning
confidence: 99%
“…3-MA treatment is associated with increased lysosomal pH and decreased lysosomal density and with inhibition of late endosome to lysosome transport (Caro et al, 1988;Punnonen et al, 1994), which may explain the slight enlargement of LAMP-2-positive structures in both GlcNAc-TV-transfected and untransfected Mv1Lu cells ( Figure 6, B and D). Nevertheless, 3-MA treatment of GlcNAc-TV transfectants results in the disappearance of large LAMP-2-labeled vacuoles corresponding to MLBs as well as the significant reduction in morphologically identifiable MLBs by electron microscopy.…”
Section: Biogenesis Of Mlbs Via Autophagymentioning
confidence: 98%
“…83 Secondly, 3-MA is not a pharmacologically potent compound, and is commonly utilized at millimolar concentrations; at these concentrations, additional effects have been reported, including the inhibition of Jun N-terminal kinase (JNK) and p38 kinase, both of which are involved in the regulation of stress-induced cell death. 84,85 Clearly, more specific loss-of-function approaches to interrogate the role of various atg genes in cell death have been long overdue. As discussed in the previous section, several studies have identified the www.landesbioscience.com Autophagyrequirement for atg orthologues in certain cell death processes.…”
Section: Evidence Against Autophagy As a Contributor To Programmed Cementioning
confidence: 99%